ENTERPRISE RISK MANAGEMENT (ERM) DAN KUALITAS LAPORAN KEUANGAN BUMN DI INDONESIA - Aviani Widyastuti (Jurnal Akuntansi Trisakti, 2020)
This study aims to see how disclosure of Enterprise Risk Management (ERM) to SOEs in Indonesia influences the quality of financial statements. In addition, to see the size of the company as a moderator in strengthening the relationship of ERM disclosure to the quality of financial statements. Through this type of associative research, this study uses a sample population of all SOEs in Indonesia with a 2015-2017 observation period. Based on the regression analysis using eviews, it was found that the ERM disclosure on SOEs had a negative effect on the quality of financial statements because the composition of the largest shares in SOEs was the government itself so there were many interests and also government intervention in it. In addition, company size in research strengthens the relationship of ERM disclosure to the quality of financial reports. This is because large companies tend to disclose ERM in order to gain the trust of stakeholders.Key Words : Enterprise Risk Management, Quality of Financial Statements, SOEs